PENGARUH ORANG TUA DALAM PEMBELAJARAN DI RUMAH SELAMA PANDEMI COVID 19 DENGAN METODE KUALITATIF - shintanuriyah shinta nuriyah; Yeni Lutfiatin Dewi Aisyah; Alfira Ayu Talita Umma; Ardianti Agustin (Jurnal Gesi, 2023)
The world was facing a major outbreak, namely Covid 19, Indonesia was also one of the countries exposed to this virus. All aspects of life have changed from normal conditions, many activities have stopped, one of which was the learning process at school. Student learning activities at school have moved into learning activities at home. Parents replace the role of school teachers in guiding and accompanying during the learning process. The purpose of this study was to determine the influence of parents in learning at home during the COVID-19 pandemic, the research method used was a qualitative method of case study approach with interview techniques to research subjects, namely parents, the research subject involved 3 parents. The results showed that the research findings were based on the data obtained that parents in student learning at home during the COVID-19 pandemic were said to have an influence when parents helped children in learning at home during the COVID-19 pandemic, which means that the role of parents were needed for the learning process of children during the study. from home, the role of parents were quite large in learning not only as a companion but also as an educator who replaces the role of teachers at schoolKeywords: parents, learning, covid 19